Attention-deficit/hyperactivity disorder management: A biopsychosocial model - Daniel, Reeba Ann (Indian Journal of Child Health, 2020)
Attention-deficit/hyperactivity disorder (ADHD) is the most common neurobehavioral disorder of childhood. It represents a complex problem because it appears at an early age, affects the daily lives of children from all areas of development, and is likely to persist throughout the life. The main management interventions in ADHD include pharmacotherapy, behavioral management, and family therapy which vary in their precedence according to age of the child and degree of impairment in the child. The biopsychosocial model tries to elucidate the interactions between biological, psychological, and social factors which determine the cause, manifestation, and outcome of any disease. In this article, we discuss how the biopsychosocial model of disease can be applied to ADHD to explain the symptoms as well as how it can help in planning of management at individual level.